Rancang Bangun Sistem Informasi pada Puskesmas Bara Permai Berbasis Website - Dony Tri Putra; Nirsal; Nuur Insan Tangkelangi (Ikatan Ahli Informatika Indonesia, 2024)
This study aims to build an information system at the Bara Permai Health Center in Palopo City based on a website. This application is expected to help and facilitate the archiving of patient data at the Bara Permai Health Center in Palopo City. This research was conducted at the Bara Permai Health Center in Palopo City. The type of research used in this study is Research and Development (R&D) using the waterfall research development method. The data collection methods used are observation, interviews and literature studies. The design of the system model uses the Unified Modeling Language (UML) approach consisting of Use Case Diagrams, Activity Diagrams, Sequence Diagrams, and Class Diagrams. The results of this study are in the form of an application for archiving patient data, drug data, employee data, and doctor data built using the Visual Studio Code programming language, as application creation software, XAMPP as a MySQL database web server for report generation. The testing used in this system is the white box testing technique, where all displays and features in this system have functioned well so that this application can be used at the Bara Permai Health Center in Palopo City